1996
DOI: 10.1002/etc.5620150217
|View full text |Cite
|
Sign up to set email alerts
|

The effects of water chemistry on the toxicity of copper to fathead minnows

Abstract: Abstract-The effects of various water chemistry parameters on the toxicity of copper to larval fathead minnows were investigated. Increased pH, hardness, sodium, dissolved organic matter, and suspended solids each caused toxicity to decrease on the basis of total copper concentrations. In contrast, added potassium resulted in increased toxicity. Alkalinity had no observed effect on total copper LC50s, but its effects might have been masked by those of the cations added with it. In most cases, the effects of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1
10

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(103 citation statements)
references
References 44 publications
3
89
1
10
Order By: Relevance
“…Several studies demonstrated the disinfecting role of potassium permanganate and copper sulfate in aquaculture (Plumb 1992;Phillips 1996;Hasan and Ahmed 2002;Faruk et al 2005;Mitchell et al 2008). Nevertheless, the disinfecting action of these chemicals is dependent to the water alkalinity, water hardness, pH, dosage and duration of treatment (Palmer 1962;Tucker and Robinson 1990;Peres and Pihan 1991;Straus and Tucker 1993;Erickson et al 1996;Straus 2004;Carvalho and Fernandes 2006). In our study, the bacteria load of the skin reduced as the copper sulfate concentrations elevated from 1 to 15 mg/l.…”
Section: Discussionsupporting
confidence: 48%
“…Several studies demonstrated the disinfecting role of potassium permanganate and copper sulfate in aquaculture (Plumb 1992;Phillips 1996;Hasan and Ahmed 2002;Faruk et al 2005;Mitchell et al 2008). Nevertheless, the disinfecting action of these chemicals is dependent to the water alkalinity, water hardness, pH, dosage and duration of treatment (Palmer 1962;Tucker and Robinson 1990;Peres and Pihan 1991;Straus and Tucker 1993;Erickson et al 1996;Straus 2004;Carvalho and Fernandes 2006). In our study, the bacteria load of the skin reduced as the copper sulfate concentrations elevated from 1 to 15 mg/l.…”
Section: Discussionsupporting
confidence: 48%
“…This is consistent with the studies for Ni toxicity by Lock et al (2007b) and also for some other metals (de Schamphelaere and Janssen 2002; Heijerick et al 2002b;Lock et al 2007a). However, more previous studies have observed a significant correlation between EC50 and pH at EC50 (Erickson et al 1996;Heijerick et al 2002a;Parker et al 1998;Thakali et al 2006a, b;Voigt et al 2006). Hence, incorporation of proton competition into the concept of BLM remains to be justified (Wang et al 2009).…”
Section: Variation and Prediction Of Ni Ec50mentioning
confidence: 96%
“…Several studies demonstrated the disinfecting role of potassium permanganate and copper sulfate in aquaculture (Plumb Plumb 1992;Phillips 1996;Hasan and Ahmed 2002;Faruk et al 2005;Mitchell et al 2008;Farmer et al 2012). Nevertheless, the disinfecting action of these chemicals is dependent to the water alkalinity, water hardness, pH, dosage and duration of treatment (Palmer 1962;Tucker and Robinson 1990;Peres and Pihan 1991;Straus and Tucker 1993;Erickson et al 1996;Straus 2004;Carvalho and Fernandes 2006). In our study, the increase of copper sulfate doses from 0.07 to 0.5 mg/l did not have obvious impact on the bacterial load of giil, skin and fish surrounding water compared to control.…”
Section: Discussionmentioning
confidence: 99%